Hi, I was wondering can you show me how to convert this form of the equation:
(2 (4 n - 3 n^2))/(1 - n)^3 + (4 - 6 n)/(1 - n)^2to this form:
(2 (n-2))/(n-1)^3Thank you
$\displaystyle \displaystyle\frac{2(4n - 3n^2)}{(1 - n)^3} + \displaystyle\frac{4 - 6n}{(1 - n)^2}$
$\displaystyle = \displaystyle\frac{2(4n - 3n^2) + (4 -6n)(1 - n)}{(1 - n)^3}$
$\displaystyle = \displaystyle\frac{8n - 6n^2 + 4 - 10n + 6n^2}{(1 - n)^3} = \displaystyle\frac{4 - 2n}{(1 - n)^3} = \displaystyle\frac{2(n - 2)}{(1 - n)^3}$